Paper Review On The Relationship Between Transformational Leadership And Readiness For Change - Ali Al-Tahitah; Mohamed Mihlar Abdul Muthaliff; Mohammed Abdulrab; Qais Ahmed Al-Maamari (American Association for Science and Technology, 2024)
Non-Indexed Publication